Risk Factors of Musculoskeletal Disorders in Office Workers - Priska Aulianingrum; Hendra Hendra (Universitas Airlangga, 2022)
Introduction: Musculoskeletal disorders (MSDs) are a collection of symptoms in the human skeletal and muscular systems, which are characterized by discomfort or pain. The International Labor Organization (ILO) stated that MSDs are the most common health problem among office workers in 27 countries under the European Union. Therefore, this study aims to determine the risk factors for MSDs among office workers. Method: This study used the literature review method by accessing an online database using different keywords, namely risk factors, musculoskeletal disorders, and office workers. Subsequently, 939, 1,421, and 243 articles were obtained from Google Scholar, ProQuest, and PubMed.Gov, respectively, with a total of 2,603. The inclusion criteria include papers published between 2011 and 2021, relevant titles and abstracts, primary study with a cross-sectional design, as well as full-text availability. Incomplete articles that are irrelevant to the topic were then excluded, after which a total of eight were selected for analysis. Result: Based on selected articles known that the risk factors for MSDs include age, gender, knowledge of ergonomics, work posture, work facilities, duration of work, physical activity, and psychosocial factors in the workplace. Conclusion: The significant risk factors for MSDs include increasing age, female gender, increased work duration, poor knowledge of ergonomics, wrong work posture, non-ergonomic support facilities, lack of physical activity, as well as poor psychosocial conditions in the workplace.